Sustainable Development Goals: Literasi Digitalisasi Keuangan Usaha Mikro, Kecil dan Menengah (UMKM) di Kota Palangka Raya - Rakhmawati, Dewi; Nugroho, Sanjayanto; Eriawaty, Eriawaty (Universitas Batanghari Jambi, 2025)
This research aims to analyze the influence of digitalization of Micro, Small and Medium Enterprises (MSMEs) and financial literacy on the implementation of Sustainable Development Goals (SDGs), using the SEM-PLS method with 100 MSME respondents in Palangka Raya who were involved in this research. The research results show that both factors, digitalization and financial literacy, have a significant influence on the implementation of SDGs, SDG Goal 8 (Decent Work and Economic Growth), and SDG 9 (Industry, Innovation and Infrastructure) in Palangka Raya.